2019
DOI: 10.2174/1874372201913010058
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Linear Discoid Lupus Erythematosus of Scalp Following Lines of Blaschko

Abstract: Discoid lupus erythematosus (DLE) is an inflammatory autoimmune disease leading to scarring and hair loss. Linear Discoid lupus erythematosus has been mentioned in the literature as a rare variant. This article describes isolated linear DLE of the scalp. We present a 26-year-old Saudi male who had unilateral linear DLE of the scalp with no involvement of other body sites and no systemic manifestations. This case is the first case of isolated linear DLE on the scalp. This presentation should be considered as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Features suggestive of active LE in our patient were linear vessels, structureless white areas, white scales, and follicular plugs. Similar features have been described in two cases of linear LE 7,8 . Dermoscopic features reflecting long‐standing disease are reticulate pigmentation, pigment granules, and white structureless areas 2,5 …”
Section: Discussionsupporting
confidence: 62%
“…Features suggestive of active LE in our patient were linear vessels, structureless white areas, white scales, and follicular plugs. Similar features have been described in two cases of linear LE 7,8 . Dermoscopic features reflecting long‐standing disease are reticulate pigmentation, pigment granules, and white structureless areas 2,5 …”
Section: Discussionsupporting
confidence: 62%
“…Vessels. Arborizing red lines were observed in 65/157 (41.4%) patients [4,28,33,36,[47][48][49][50]53].…”
Section: Discoid Lupus Erythematosusmentioning
confidence: 98%
“…Twelve original studies and 6 case reports, including a total of 157 patients, reported on trichoscopy in discoid lupus erythematosus [4,17,28,29,33,36,44,[47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discoid Lupus Erythematosusmentioning
confidence: 99%
See 1 more Smart Citation